Intestinal obstruction induced by a giant incarcerated Spigelian hernia: Case report and review of the literature - Ribeiro, Edson Augusto; Cruz Junior , Ruy Jorge; Moreira , Samuel Martins (São Paulo Medical Journal, 2005)
CONTEXT: Spigelian hernia is an uncommon spontaneous lateral ventral hernia with an incarceration ratio oi around 20%. However, complications such as intestinal obstruction are ex!remely rare. We report on a case oi giant incarcerated Spgelian hernia with a clinicai condition oi complete intestinal obstruction that was treated using prosthetic polypropylene mesh. CASE REPORT: A 72-year-old woman was admitted to the emergency department complaining oi dilluse abdominal pain. Abdominal exam ination revealed a lirm 1 O x 1 O cm tender mass in the lower lelt quadrant, without surrounding cellulite or tenderness. Plain abdominal radiographs displayed the lormation oi leveis, thus indicating the existence oi intestinal obstruction. An abdominal computed tomography scan clearly showed a lluid and air-lilled mass in the solt tissue area oi the lower lelt-sicle abdominal wall. Spigelian incarcerated hernia was diagnosed and the patient underwent emergency surgical repa ir by means oi local incision. lhe large delect in the abdominal wall was closed up as success ive anatem icei layers, and a prosthetic polypropylene mesh was sei into the lateral aspect oi the rectus sheath. The postoperative course was uneventful and the patient was discharged on the seventh postoperative day.